Performance evaluation methods for librarians in selected colleges and university libraries in Metro Manila a survey - Elverio, Hilaria A. (1990)
This research study provides an overview of the academic libraries in Metro Manila which conduct performance evaluations of their librarians. Specifically, the survey reviews the reasons for and the manner of conducting performance appraisals, the different appraisal methods used, and the problems encountered with the different appraisal methods used including the potential pitfalls of performance evaluations. Thirty-three selected college and university libraries in Metro Manila served as the respondent intitutions for the study. The study used the descriptive survey method of research. The survey questionnaire was the instrument used in gathering the data.